Seed Source Variation in Pod and Seed Characteristics of Acacia nilotica subsp. Indica - Ahlawat, S P; Kumar, R V; Gupta, V K (Annals of Arid Zone, 2016)
A study was conducted on seed source variation in pod and seed characters of Acacia nilotica ssp. indica. Germplasm was collected from 28 provenances of Central and North-western parts of India, lying between 75°39'E to 81°39'E longitude and 20042'N to 25°27'N latitude. and under 18 seed zones of six states of the country. Findings revealed significant variation within and between provenances for pod length. pod width. number of seeds per pod, seed length, seed width, seed thickness. IOO-seed weight and IOO-seed volume. Significant positive correlations were found between tree height and clean bole and tree girth. pod length and seeds per pod, seed weight and seed length, width and thickness, seed weight and seed volume, seed volume and seed length, width and thickness. It indicated that improvement in pod length and seed weight will improve the other associated traits. Raipur, Kawardha and Mandla seeds sources had high seed weight with bold seeds and hence they would be best for raising the nursery. Selection of plus trees from these provenances can bring higher genetic gain and improvement in these trai ts. Key words: Acacia nilotica, correlation, provenance, pod and seed size, variability.